Tertiary lymphoid structures correlate with the therapeutic efficacy and prognosis of resectable esophageal squamous cell carcinoma undergoing neoadjuvant chemoradiotherapy plus immunotherapy - Zhai, Ke; Xie, Ru; Ru, Kun; Zhao, Miaoqing (Frontiers in Immunology, 2025)
BackgroundTertiary lymphoid structures (TLSs) are linked to prognosis in esophageal squamous cell carcinoma (ESCC), but whether the distribution, abundance, and maturity of TLSs affect therapeutic efficacy and prognosis in ESCC treated with neoadjuvant chemoradiotherapy plus immunotherapy (NRCI) remains unclear. We explored TLS characteristics and correlated them with patient survival.MethodsA total of 157 resectable ESCC patients treated with neoadjuvant therapy between September 2020 and May 2023 were divided into NRCI (n=49) and neoadjuvant chemoimmunotherapy (NCI, n=108) groups. Multiplex immunofluorescence (mIHC) was employed to compare the spatial distribution and cellular composition of TLSs in the NRCI (n=40) and NCI (n=40) groups. A TLSs scoring system assessed TLSs abundance and maturity across intratumoral regions (T regions), invasive margins (IM regions), and peritumoral regions (P regions). The differences in overall survival (OS) and disease-free survival (DFS) between the two groups were analyzed. Furthermore, whole-exome sequencing (WES) on 20 untreated ESCC samples examined the relationship between TLS infiltration and genetic mutations.ResultsThe OS and DFS in the NRCI group were significantly superior to the NCI group, with a higher rate of major pathological response (MPR). MPR patients exhibited significantly longer OS and DFS, suggesting that NRCI therapy substantially enhanced patient outcomes (all P<0.05). TLSs abundance exhibited varying immune effects in different tissue regions: intratumoral and invasive margin TLSs abundance was significantly associated with longer OS, while peritumoral TLSs abundance was linked to a shorter OS (all P<0.05). Highly mature TLSs (M-TLSs) were closely associated with a better OS (all P<0.05). In the NRCI group, M-TLSs showed higher proportions of CD20+Ki-67+ B cells, CD21+ dendritic cells (DCs), CD4+Ki-67+ helper T cells (Th), and CD8+Ki-67+ cytotoxic T cells compared to the NCI group (all P<0.05), indicating that NRCI therapy enhanced antitumor immune responses.ConclusionNRCI therapy significantly enhanced the prognosis of resectable ESCCs compared to NCI therapy. The distribution and abundance of TLSs were clearly associated with OS in ESCCs and acted as independent prognostic indicators for OS in NRCI therapy. NRCI therapy extended OS and bolstered antitumor immune responses by facilitating the proliferation and activation of M-TLSs.